2006
DOI: 10.1242/jcs.03082
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of MAPK in mature oocytes triggers progression into mitosis via a Ca2+-dependent pathway but without completion of S phase

Abstract: Unfertilized sea urchin eggs that are arrested at G1 phase after completion of meiosis contain a highly phosphorylated mitogen-activated protein (MAP) kinase (MAPK), the ERK-like protein (ERK-LP). Several data including our previous results show that ERK-LP is inactivated after fertilization, which agrees with results obtained in other species including Xenopus, starfish and mammals. The question is to elucidate the function of a high MAPK activity in sea urchin eggs. We report here that dephosphorylation of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 58 publications
5
26
0
1
Order By: Relevance
“…In Xenopus, Cdc6 is the missing factor in immature oocytes (17), and cyclin E is necessary for DNA replication in egg extracts (18), whereas the Mos-MAPK-Rsk pathway is unlikely to play any role for progression through G1 phase due to its preceding inactivation (19,20). In sea urchin eggs, which also arrest at G1 phase until fertilization, conflicting reports have accumulated: MAPK inactivation is necessary for DNA replication (21); Cdk activity is not required for DNA replication (22,23); MAPK inactivation does not cause DNA replication (24); and MAPK activation and cyclin E are required for DNA replication (25). No study, however, examined the immediate downstream of MAPK or the behavior of Mcms and Cdc45, excluding further comparison with starfish egg system.…”
Section: Discussionmentioning
confidence: 99%
“…In Xenopus, Cdc6 is the missing factor in immature oocytes (17), and cyclin E is necessary for DNA replication in egg extracts (18), whereas the Mos-MAPK-Rsk pathway is unlikely to play any role for progression through G1 phase due to its preceding inactivation (19,20). In sea urchin eggs, which also arrest at G1 phase until fertilization, conflicting reports have accumulated: MAPK inactivation is necessary for DNA replication (21); Cdk activity is not required for DNA replication (22,23); MAPK inactivation does not cause DNA replication (24); and MAPK activation and cyclin E are required for DNA replication (25). No study, however, examined the immediate downstream of MAPK or the behavior of Mcms and Cdc45, excluding further comparison with starfish egg system.…”
Section: Discussionmentioning
confidence: 99%
“…According to all of these results, our previous work showed that unfertilized sea urchin eggs also contain a high MAPK1/3 activity that is inactivated after fertilization, 22,23 but other authors detected in these eggs an MAPK1/3 protein that is not active. 24 We also previously reported that artificial inactivation of MAPK1/3 triggers entry into M phase as in other species, 25 but it was not known whether this condition also induced progress into embryonic development as described above for starfish or ascidian. All these data prompted us to investigate in the sea urchin model how the MAPK1/3 signaling cascade may link cell cycle progression and the triggering of cell death in unfertilized eggs.…”
Section: Introductionmentioning
confidence: 87%
“…25 We investigated whether these eggs would be capable of entering embryonic development. Five eggs were recorded for longer durations under a video-microscope; one is shown (Fig.…”
Section: Inactivation Of the Map2k-mapk1/3 Cascade In Unfertilized Egmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilization promotes Ca 2+ -dependent degradation and/or inactivation of upstream kinases Mos and MAPKK, and triggers a rapid dephosphorylation/inactivation of all MAPK (inactivation of cytostatic factor). In the actively dividing embryos, a fraction of MAPK will be transiently activated at mitotic phase, and thereafter serves as a component of checkpoint (Chesnel et al 1997;Chung et al 1991;Eckberg 1997;Fabian et al 1993;Ferrell 1999;Ferrell et al 1991;Gavin et al 1999;Git et al 2009;Gross et al 2000;Huo et al 2004;Ito et al 2010;Iwasaki et al 2008;Katsu et al 1999;Keady et al 2007;Kosako et al 1992; Lee et al 2006;Lu et al 2002;Palmer et al 1998;Philipova and Whitaker 1998;Sackton et al 2007;Sadler et al 2004;Sasaki and Chiba 2004;Sato et al 2001;Sato et al 2003;Sato et al 2000;Shibuya et al 1992;Shibuya et al 1996;Stricker 2009;Sun et al 1999;Tokmakov et al 2005;Verlhac et al 1996;Zhang et al 2006). …”
Section: Mitogen-activated Protein Kinase (P42/p44mapk/erk)mentioning
confidence: 99%